Influence of transport and time on blood variables commonly measured for the athlete biological passport. Issue 2 (29th April 2015) - Robinson, Neil; Giraud, Sylvain; Schumacher, Yorck Olaf; Saugy, Martial
Abstract : Some recent studies have characterized the stability of blood variables commonly measured for the Athlete Biological Passport. The aim of this study was to characterize the impact of different shipments conditions and the quality of the results returned by the haematological analyzer. Twenty‐two healthy male subjects provided five EDTA tubes each. Four shipment conditions (24, 36, 48, 72 h) under refrigerated conditions were tested and compared to a set of samples left in the laboratory also under refrigerated conditions (group control). All measurements were conducted using two Sysmex XT‐2000i analyzers. Haemoglobin concentration, reticulocytes percentage, and OFF‐score numerical data were the same for samples analyzed just after collection and after a shipment under refrigerated conditions up to 72 h. Detailed information reported especially by the differential (DIFF) channel scatterplot of the Sysmex XT‐2000i indicated that there were signs of blood deterioration, but were not of relevance for the variables used in the Athlete Biological Passport. As long as the cold chain is guaranteed, the time delay between the collection and the analyses of blood variables can be extended. Copyright© 2015 John Wiley & Sons, Ltd. Abstract : Under our experimental conditions, the variables used in the Athlete Biological Passport were stable up to 72 hours. Minor signs of blood deterioration could be observed only for some blood samples in the white blood cell differential channel scatterplot reported by the Sysmex XT‐2000i.